The Use of Brain Computer Interface in the Intervention of People with Post-Stroke Aphasia: A Systematic Review - Branquinho, Ana Sofia (2025)
Introduction: Post-stroke aphasia has a significant impact on the quality of life of the person with this disorder and on the resources required in the health sector. There has been growing interest in investigating new intervention methodologies, such as those that integrate brain computer interface (BCI) technology. The aim of this paper is to analyse how the use of this technology in a therapeutic context can enhance the recovery of language and communication skills in people with aphasia. Method: Systematic literature review using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, involving searches in the PubMed Central, SciELO, LILACS, Web of Science databases and the databases integrated into the EBSCO HOST platform, with no time or language restrictions, using MeSH (Medical Subject Headings) and entry terms in English. The study selection process was carried out independently by two of the authors through the Rayyan® software. The evidence analysis of the eligible studies in screening was carried out using the John Hopkins model of levels of evidence and quality of studies. Results: A total of 198 articles were obtained, of which four were included in this systematic review after eliminating duplicates and applying the eligibility criteria. Therapeutic intervention based on a BCI system could strengthen the linguistic network and rebalance the functional networks of people with aphasia, due to the neurofeedback mechanism it provides. Some authors encourage the development of BCI systems with the integration of different techniques (such as functional magnetic resonance imaging in combination with electroencephalography). Research in this area is recent, and studies are scarce and mostly quasi-experimental. The articles included in this review have a low quality of evidence. Conclusion: The use of brain computer interface systems could have a positive influence on the language and communication rehabilitation of people with aphasia. However, the integration of this recent technology into therapeutic intervention still faces several challenges, and more robust studies are needed to create specific protocols and clinical guidelines.